ANALISIS LUAS POTENSI LAHAN IRIGASI BERDASARKAN NERACA AIR EMBUNG KEMBANGAN - Muhardiono, Iman; Arthamefia, Diva (JURNAL SUMBER DAYA AIR, 2024)
Pule District, Trenggalek Regency, East Java Province has only 42% of rice fields with irrigated status, and 58% of non-irrigated land. With the presence of a reservoir. the area of non-irrigated rice fields can be served and the planting indeks of rice fields can be increased. To be able to meet the target area of irrigated land diverted by reservoir, a hydrological and water balance approach is needed. The aim of this study is to analyze the water balance of reservoir to obtain the volume of water and the area of rice fields that can be irrigated each month. By using F.J.Mock to analyse water balance and calculate mainstay discharge. Evapotranspiration is calculated by Penman Modified method. The highest mainstay discharge Q80 is occurred about 3.25 m3/s in January, meanwhile the lowest is 0.22 m3/s in October. Reservoir capacity is determined from maximum volume based on height of reservoir. The height is 13.20 m which referenced to elevation 552.20 m.s.l. Maximum volume of reservoir is 56,437 m3. Analysis results show the highest inflow discharge is occurred in January about 7.46 million m3/month, the lowest in August about 0.45 million m3/month. Those condition of discharge if utilized for irrigation 11 Ha around 44,533 m3/month and raw water 2,560 people around 11,904 m3/month, so the reservoir is still in a fulfilled condition. The lowest inflow discharge can be referenced to determine maximum potential irrigation covered  area  into 112 Ha in dry season.    Keywords: reservoir, irrigation, water balance, water harvesting, land large